FTO in cancer: functions, molecular mechanisms, and therapeutic implications - Li, Yangchan; Su, Rui; Deng, Xiaolan; Chen, Yong; Chen, Jianjun (Trends in cancer, 2022)
N -methyladenosine (m A) is the most abundant internal modification in mRNA that affects RNA processing, stability, and translation. Discovered as the first RNA m A demethylase, the fat mass and obesity-associated protein (FTO) is frequently dysregulated and plays important roles in various types of cancers. Targeting FTO holds promising therapeutic significance via suppressing tumor growth, potentiating immunotherapy, and attenuating drug resistance. Here, we review recent advances in our understanding of the functions and underlying molecular mechanisms of FTO in tumor development, cancer stem cell (CSC) self-renewal, microenvironment regulation, immunity, and metabolism and discuss the therapeutic potential of targeting FTO for cancer treatment.